Ensuring Reliability: Adaptation and Validation of the AI Anxiety Scale (AIAS) in Indonesia - Ramadini, Shifa; Pratiwi, Ratri (Journal of Psychological Perspective, 2025)
This study aims to adapt Wang and Wang’s Artificial Intelligence Anxiety Scale (2019) into the context of Indonesian culture and language. The research involved 222 respondents, consisting of 89 males and 133 females, aged between 15 and over 35 years old. The adaptation process followed six stages: (1) initial translations by translators with different backgrounds, (2) synthesis of the translations into a single version, (3) back-translation by native speakers of the source language, (4) content validation by an expert committee, (5) testing the pre-final version on relevant subjects, and (6) submission of documentation for evaluation. Reliability testing was conducted using Cronbach’s alpha, while logical validity was assessed with Aiken’s V and construct validity using confirmatory factor analysis (CFA). The results indicated that the adapted scale had high reliability, with a Cronbach’s alpha value of 0.916, and adequate validity, with an Aiken’s V value greater than 0.50. The confirmatory factor analysis demonstrated a good model fit, with an RMSEA value of 0.066, CFI of 0.938, and TLI of 0.927. The Indonesian version of the Artificial Intelligence Anxiety Scale is deemed valid and reliable, making it suitable for use in Indonesia